Democratic Republic of the Congo Student Assessment : SABER Country Report 2014 - World Bank Group (World Bank, Washington, DC, 2016)
The Democratic Republic of the Congo (DRC) has focused on increasing student learning outcomes by improving the quality of education in the country. An effective student assessment system is an important component to improving education quality and learning outcomes as it provides the necessary information to meet stakeholders’ decision-making needs. In order to gain a better understanding of the strengths and weaknesses of its existing assessment system, DRC decided to benchmark this system using standardized tools developed under The World Bank’s Systems Approach for Better Education Results (SABER) program. SABER is an evidence-based program to help countries systematically examine and strengthen the performance of different aspects of their education systems. The key policy areas for this students assessment are as follows: (i) Classroom Assessment; (ii) Examinations; (iii) National Large-Scale Assessment (NLSA); and (iv) International Large-Scale Assessment (ILSA).